Uwarunkowane litopedogenicznie rozmieszczenie Cu, Ni i Zn w profilach leśnych gleb rdzawych i glejobielicowych terasy nadzalewowej Słupi - Jonczak, Jerzy (Leśne Prace Badawcze, 2014)
The aim of the study was to assess the influence of lithological and pedogenic factors in the shaping of Cu, Ni and Zn distribution patterns in the profiles of Brunic Arenosols and Gleyic Podzols of the lower supra-flood terrace of the Słupia River, which is located outside the range of significant anthropogenic sources of pollution with these metals. The contents of the investigated metals were analyzed in aqua regia extracts of samples collected from three profiles of Brunic Arenosols, composed of river sands, and three profiles of Gleyic Podzols, composed of river sands transformed by eolian processes. In general, river sands contained higher amounts of Ni and Zn (2.6–6.9 mg·kg -1 Ni; 10.3–16.2 mg·kg -1 Zn) compared to eolian sands (1.2–2.4 mg·kg -1 Ni; 3.3–17.3 mg·kg -1 ), while the content of copper tended to be higher in eolian sands (1.3–1.9 mg·kg -1 ) than river sands (0.1–1.5 mg·kg -1 ). The observed differences between the two types of sand are due to the loss of fine granulometric fractions and various minerals during eolian processes. Higher concentrations of the investigated metals in soil solum as compared to parent material are due to their uptake from deeper parts of the soil by roots and subsequent return to the soil surface by litter fall. Therefore, the highest concentrations of Cu, Ni and Zn were observed in ectohumus. In the mineral component of the soil, the highest concentrations were observed in organic matter-rich A and B horizons, which indicate close interactions between heavy metals, humic substances and iron oxides. The vertical distribution of the investigated metals in the profiles of Gleyic Podzols indicates their leaching during podzolization. The observed contents of Cu, Ni and Zn, both in Brunic Arenosols and Gleyic Podzols, were lower than the geochemical background, which confirms that anthropogenic contamination of the studied area with these metals is marginal.